PENGEMBANGAN KONSEP KEBERLANJUTAN LINGKUNGAN DENGAN PENDEKATAN ASSET BASED COMMUNITY DEVELOPMENT (STUDI KASUS DI UIN SUNAN AMPEL SURABAYA) - Erry Ika Rhofita (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
The environment sustainability concepts is one of commitments at Islamic State University Sunan Ampel Surabaya (UINSA). The purposes of this study were knowing and developing of the environment sustainability concept at UINSA with approach Asset Based Community Development (ABCD), by the university facilities and infrastructure optimizing, the potential and the strength of the university. This study used a Combination Research Methods (Mixed Methods) were a methods that used quantitative and qualitative approach in the research activities. Qualitative approach were used to obtain the data from the parties that have the authority to take decisions (stakeholders). While the quantitative approach used to obtain the data from the environment university users (lecturers, staffs, and students). Data collection methods with interviews, observation, focus group discussions (FGD), literature study, and documentation. The results of this study were; 1) UINSA has potential and a major force in the development of the concept of environmental sustainability in the areas of the three responsibilities of Higher Education, UCE, and human resources, as written in the University's Strategic Plan and UCE Strategic Plan year 2014-2019, 2) concept environmental sustainability is a manifestation of the university's commitment to implement the teachings of Islam Rahmatan Lil Alamin applied in every activity of the three responsibilities of Higher Education, UCE and environment management at university, that it embodied in the form of environmental sustainability policy, 3) stakeholders and users have high expectations regarding sustainability environment concept and can be used to realize the green campus programs.